No detection of TSH or TSHR in oral lichen planus lesions in patients with or without hypothyroidism. (3rd July 2020) - Vehviläinen, Mari; Salem, Abdelhakim; Asghar, Muhammad Yasir; Salo, Tuula; Siponen, Maria
Abstract: Objective: An association between hypothyroidism (HT) and oral lichen planus (OLP) has been reported. However, the mechanisms that could explain this association remain unresolved. This study aimed to evaluate the expression of thyroid-stimulating hormone (TSH) and thyroid-stimulating hormone receptor (TSHR) in healthy oral mucosa and in OLP lesions of individuals with and without HT. Material and methods: Immunohistochemical expression of TSH and TSHR was studied in oral mucosal biopsies obtained from 14 OLP patients with HT, 14 OLP patients without HT and 10 healthy controls without oral mucosal lesions. Gene expression of TSHR was investigated by using three different PCR techniques in oral mucosal samples from 7 OLP patients with HT, 3 OLP patients without HT, 9 healthy controls and in cultured human oral epithelial cells. Gene expression of TSH was examined by employing 2 PCR techniques in oral mucosal samples from 2 OLP patients with HT, 2 OLP patients without HT and 4 healthy controls. Results: TSH and TSHR stainings were negative in the studied oral mucosal specimens. Gene quantification assays demonstrated negative gene expression of TSH and TSHR in clinical and in vitro samples. Conclusions: These results suggest that TSH and TSHR may not be commonly involved in the pathogenetic mechanism that could explain the association between OLP and hypothyroidism.